Gender Differences and the Impact of Partnership and Children on Quality of Life During the COVID-19 Pandemic - Nora Hettich-Damm; Juila Petersen; Daniela Zahn; Rieke Baumkoetter; Rieke Baumkoetter; Philipp S. Wild; Philipp S. Wild; Philipp S. Wild; Philipp S. Wild; Thomas Muenzel; Andreas K. Schuster; Jochem Koenig; et al. (Frontiers Media S.A., 2023)
Objectives: The COVID-19 pandemic and its protective measures have changed the daily lives of families and may have affected quality of life (QoL). The aim of this study was to analyze gender differences in QoL and to examine individuals living in different partnership and family constellations.Methods: Data from the Gutenberg COVID-19 cohort study (N = 10,250) with two measurement time points during the pandemic (2020 and 2021) were used. QoL was assessed using the EUROHIS-QOL questionnaire. Descriptive analyses and autoregressive regressions were performed.Results: Women reported lower QoL than men, and QoL was significantly lower at the second measurement time point in both men and women. Older age, male gender, no migration background, and higher socioeconomic status, as well as partnership and children (especially in men), were protective factors for QoL. Women living with children under 14 and single mothers reported significantly lower QoL.Conclusion: Partnership and family were protective factors for QoL. However, women with young children and single mothers are vulnerable groups for lower QoL. Support is especially needed for women with young children.